Environmental Literacy Training for Citizen Groups - Sullivan, Bruce D. (University of Wisconsin-Stevens Point, College of Natural Resources, 1981)
An Environmental Literacy Training (ELT) model was developed through the use of existing literature, contacts with numerous professionals and the experience of the writer. The goals of the ELT model were to identify goals, guidelines and procedures for an adult environmental education program model which would facilitate the development of environmentally literate citizens and to provide a framework through which a citizen group could develop an ELT program that is consistent with its own goals and needs. The ELT model was designed to facilitate the development of environmental literacy by providing a framework through which citizen groups could design, implement and evaluate a community environmental action project. The components of this program model are: 1. Identification of a local environmental issue. 2. Investigation of the issue. 3. Selection of an action project. 4. Design of.an action strategy. 5. Design of learning experiences. A. Diagnosis of learning needs. B. Preparation of learning objectives. C. Selection of specific learning experiences. D. Development of learning evaluation procedures. 6. Integration of the action strategy and learning experiences. 7. Implementation of the ELT program. 8. Evaluation of the overall program. It is hoped that through the use of this program model, citizens could gain the skills and motivation necessary to influence societal decisions to achieve or maintain a high level of environmental quality.